How do you simplify i^6(2i-i^2-3i^3) ?

2 Answers

The answer is -1-5i

Explanation:

First we factorize powers of i.So i^6 would become -1. 3i^3 would become -3i and i^2 would become -1.By putting values
-1(2i-(-1)+3i). Now -1(2i+3i+1) would become -1(5i+1) and then -5i-1
I HOPE IT HELPS:)

Mar 12, 2018

See details below

Explanation:

Expand expresion.

i^6(2i-i^2-3i^3)=2i^7-i^8-3i^9

But we know that:

i^1=i
i^2=-1 (by definition)
i^3=i^2·i=-i
i^4=i^2·i^2=(-1)·(-1)=1
i^5=i^4·i=1·i=i and starts again
i^6=i^5·i=i·i=i^2=-1
i^7=i^6·i=-i

for this cliclic result, we can write:

i^6(2i-i^2-3i^3)=2i^7-i^8-3i^9=-2i-1-3i=-1-5i